2019
DOI: 10.1186/s13104-019-4317-x
|View full text |Cite
|
Sign up to set email alerts
|

Scabies outbreak investigation and risk factors in Kechabira district, Southern Ethiopia: unmatched case control study

Abstract: Objective Scabies is an infection of the skin, which caused by human itch mite Sarcoptes scabiei . It is a common health problem in Ethiopia, especially during disasters, poor sanitation and overcrowded living condition. However, investigation on scabies outbreak and associated factors was absent or scarce in the country in general and in the study area in particular. Hence, this study was intended to investigate scabies outbreak, identify risk factors, and recommend pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
25
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 24 publications
16
25
4
3
Order By: Relevance
“…Furthermore; we have conducted a sensitivity analysis by the JBI quality score, which is categorized as "good quality" (JBI quality score equal to or above 5) and "low quality" (JBI quality score less than 5). We found that only one study, which has low quality in this review (JBI quality score = 4) [14]. Consequently, the pooled prevalence of scabies was 16.3% (95% CI; 4.2, 28.3) after removing a study which has low quality.…”
Section: Sensitivity Analysismentioning
confidence: 78%
See 4 more Smart Citations
“…Furthermore; we have conducted a sensitivity analysis by the JBI quality score, which is categorized as "good quality" (JBI quality score equal to or above 5) and "low quality" (JBI quality score less than 5). We found that only one study, which has low quality in this review (JBI quality score = 4) [14]. Consequently, the pooled prevalence of scabies was 16.3% (95% CI; 4.2, 28.3) after removing a study which has low quality.…”
Section: Sensitivity Analysismentioning
confidence: 78%
“…Eight studies were reported the associated factors of human scabies in Ethiopia. Regarding to the prevalence of scabies, the smallest was 2.5%, which was reported a study conducted in SNNPR and the highest was 35%, which reported a study conducted in Amhara regional state [14,31]. In this review, the studies were found from only two Ethiopian regions out of nine regions and two administrative cities.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 80%
See 3 more Smart Citations